Representasi Laki-laki Ladyboy dalam Karya Tari SHEMALE: Satu Anomali dalam Prilaku Laki-laki Minangkabau - Dendi Chairi; Indrayuda Indrayuda (SENDRATASIK UNP, 2023)
This article aims to reveal the problem of deviant behavior in Minangkabau men. According to tradition and culture, Minangkabau men are men who are based on traditional behavior coded as syarak and syarak coded as khitabullah, meaning that Minangkabau men are men who behave according to Islamic customs and norms. In the dance work entitled "SHEMALE" Minangkabau men are represented as ladyboys, which in the current era are often found in urban areas, but do not apply in rural areas, because of the strong confines of village customs and norms, this behavioral anomaly cannot grow and develop. The creation method in the dance work "SHEMALE" is divided into 3 (three), namely the concept of creation, the process of creation, and the composition of the work (form structure). In the dance work "SHEMALE" it can be seen that every standard and deeply rooted social system, if maintained collectively, will be able to resist various external interventions. Apart from that, another message is that information technology can make people poisoned logically and intuitively, so that they deviate from their actual behavior. The third message is that there is no human being who cannot change, as long as the human being himself is willing to change.